2019
DOI: 10.1016/j.athoracsur.2019.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Weekend Effect in Surgery for Type A Dissection?: Results From the Nordic Consortium for Acute Type A Aortic Dissection Database

Abstract: Background. Aortic dissection type A requires immediate surgery. In general surgery populations, patients operated on during weekends have higher mortality rates compared with patients whose operations occur on weekdays. The weekend effect in aortic dissection type A has not been studied in detail.Methods. The Nordic Consortium for Acute Type A Aortic Dissection (NORCAAD) registry includes data for 1,159 patients who underwent type A dissection surgery at 8 Nordic centers during 2005 to 2014. This study is bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 17 publications
1
32
0
Order By: Relevance
“…Of these, 195 articles were excluded after the inclusion and exclusion criteria were applied. Full text of the remaining 45 papers was screened, yielding six studies to be included in the systematic review and meta‐analysis 8‐13 . The PRISMA flow chart illustrates these search results in Figure S1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these, 195 articles were excluded after the inclusion and exclusion criteria were applied. Full text of the remaining 45 papers was screened, yielding six studies to be included in the systematic review and meta‐analysis 8‐13 . The PRISMA flow chart illustrates these search results in Figure S1.…”
Section: Resultsmentioning
confidence: 99%
“…Other studies included in this systematic review did not adequately control and report on this factor. 8,10,11,13 Therefore, we acknowledge that these factors are potential confounders within this systematic review and could be further improved upon in future studies. 14,15,32 Overall, this study suggests that postoperative outcomes were comparable in IH and OOH surgery for ATAAD, with IH surgery being marginally superior for having lower 30-day mortality and AKI rates.…”
Section: Discussionmentioning
confidence: 99%
“…Recent data from the Nordic Consortium for acute type A aortic dissection registry 14 showed no difference in 30‐day mortality for patients with TAAAD who had operations at night and on the weekends versus patients who had operations during the day and on the weekdays, respectively. Our study corroborates these findings in a much larger, international sample.…”
Section: Commentmentioning
confidence: 99%
“…One might argue that for crucial surgeries like acute aortic dissection, where the mortality rate is as high as 1% to 2% per hour in the first 24 hours [ 28 ] and 20% of patients die before reaching the hospital, [ 29 ] or for different types of transplant surgeries, the consequences might be different. However, some papers [ 30 , 31 ] have concluded that the time of day of the surgery has no significant effect in acute aortic dissection type A surgery. On the contrary, higher mortality was found in the longer time interval from hospital arrival to computed tomography scanning in blunt traumatic aortic injury, [ 32 ] which is the second leading cause of death for trauma patients.…”
Section: Discussionmentioning
confidence: 99%